Compound probiotics and glycyrrhizic acid alleviate DON-induced liver damage linked to the alteration of lipid metabolism in piglets - Mengjie Liu; Guorong Yan; Juan Chang; Ping Wang; Chaoqi Liu; Qingqiang Yin; Xiaoxiang Xu (Journal of Functional Foods, 2024)
Compound probiotics are capable of effectively breaking down mycotoxins, and glycyrrhizic acid (GA) exhibits hepatoprotective properties. However, the protective efficacy and the underlying mechanism of combined intervention of GA and probiotics (GAP) on ameliorating Deoxynivalenol (DON)-induced liver toxicity remains unclear. This experiment involved 120 weaned piglets, encompassing the control group, the DON group, and the GPD group (E. faecalis and S. cerevisiae + GA + DON). Results showed that GAP significantly mitigated DON-related liver damage and oxidative stress. Furthermore, GAP inhibited the Nrf2/MAPK/NF-κB pathway, ultimately decreasing liver inflammation and apoptosis. Additionally, GAP significantly enhanced the expressions of ZO-1, GLUT2, PePT1, ASCT2, Occludin and Claudin-1. Moreover, metabolomics analysis revealed that GAP modulated lipid metabolism and mitigated liver damage by elevating serum levels of metabolites, such as phosphatidylcholine, phosphatidylethanolamine, and 3-amino-4-hydroxybenzoic acid. The research provides a theoretically based framework for using GAP to combat DON-induced hepatotoxicity in piglets.